The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1097/00000637-200112000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Twisting on Microanastomotic Patency of Arteries and Veins in a Rat Model

Abstract: The authors examined the effect of twisting on the patency of microvascular anastomoses 3 days after surgery. A total of 69 male Wistar rats were divided randomly into four groups. The femoral arteries and veins were dissected for a standard distance. A total of 69 microarteriorrhaphies and 68 microvenorrhaphies were performed at 0 deg and with twist of the vessel ends of 90, 180, and 270 deg. Three-day patency rates for arterial microanastomoses were 100% with a 0-deg twist, 80.9% with a 90-deg twist, 68.4% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 10 publications
3
53
0
Order By: Relevance
“…We agree with Topalan et al 2 that the technical faults and different species of rats used (Wistar rats in the study of Salgarello et al 4 vs. Sprague-Dawley rats in the studies of Bilgin et al, 1 Topalan et al, 2 and Izquierdo et al 3 ) may alter the final outcome because of different cross-sectional histologies of the artery: 2 these variations can explain the slightly different results reported.…”
Section: Effect Of Torsion On Microvenous Anastomotic Patency In Rat supporting
confidence: 82%
See 2 more Smart Citations
“…We agree with Topalan et al 2 that the technical faults and different species of rats used (Wistar rats in the study of Salgarello et al 4 vs. Sprague-Dawley rats in the studies of Bilgin et al, 1 Topalan et al, 2 and Izquierdo et al 3 ) may alter the final outcome because of different cross-sectional histologies of the artery: 2 these variations can explain the slightly different results reported.…”
Section: Effect Of Torsion On Microvenous Anastomotic Patency In Rat supporting
confidence: 82%
“…We agree with Topalan et al 2 that the torsion effect has no statistical meaning in terms of patency rates on a microvascular anastomosis, but we specify that this is true only for arteries, when the angle of rotation is included in the range studied: 0À270°in the study of Salgarello et al 4 and 0À360°in the study of Topalan et al, 2 with that precise length of dissection (25 mm in the study of Salgarello et al, 4 and 7.1 mm in the study of Topolan et al…”
Section: à4supporting
confidence: 81%
See 1 more Smart Citation
“…The patency rates in this current study at the end of 1 h for 90°and 180°were similar to the third-day patency rates of the study performed by Salgarello et al, which is the only previous study on the torsion of veins, done with Wistar rats. 7 But in the subsequent study, we observed that the nonpatent veins all became patent on the third day. The trombolytic process may differ in different species.…”
Section: Discussionmentioning
confidence: 75%
“…1 External compression, twisting (or torsion) of the anastomosis site, tension on the anastomosis site, and kinking of the pedicle must be avoided. [1][2][3] [Twisting and torsion are used as synonyms in medical literature, and refer to rotation, either clockwise or counterclockwise, along the longitudinal axis of the vessel lumen with the axis of rotation around the center of the vessel or anastomosis. ]…”
mentioning
confidence: 99%